Detection of Recurrent Non-Hodgkin Lymphoma on In-111 Capromab Pendetide Imaging. (July 2015) - Franc, Benjamin L.; Lin, Hank
Abstract : Abstract: A 73-year-old man presented with a rising prostate-specific antigen (PSA) level 5 years following brachytherapy for prostate cancer. In-111 capromab pendetide (ProstaScint) whole-body planar imaging revealed abnormal uptake in the right knee, localizing to a mass in the popliteal fossa on SPECT/CT. MRI showed a mass encasing the popliteal artery and vein, subsequently found to be non-Hodgkin lymphoma on biopsy. Response of the mass to chemotherapy was documented on 18 F-FDG PET/CT. Elevated In-111 capromab pendetide uptake in soft tissue can be important but unrelated to prostate cancer, as demonstrated in this case.